Tinjauan Fitokimia dan Aktivitas Antibakteri Ekstrak Etanol Biji Pepaya (Carica papaya L.) diaplikasikan untuk Sediaan Gel - Wahyuning Setyani; Jacinda Yakub; Octavianus Yandri; Viola Resti Kawan; Theresia Jenny Haryanto; I Made Myasa Darmika (Fakultas Farmasi Universitas Pancasila, 2020)
Papaya seeds has many benefits in medicine. One of the benefits that have been studied is it’s antibacterial activity against Staphylococcus aureus. This study aims to determine the phytochemical compounds of papaya seed ethanol extract and their antibacterial activity against Staphylococcus aureus bacteria. The ethanol extract of papaya seeds was obtained through maceration method using 95% ethanol as a solvent. Maceration was carried out by weighing 85 grams of simplicia powder, macerated using 500 mL of 95% ethanol then left for 4 days while stirring occasionally, then filtered to produce filtrate and residue. The remaining residue is then soaked again (remaserated) with 250 ml of 95% ethanol and left for 2 days. After 2 days, the sample is filtered to produce filtrate and residue. All filtrates were evaporated using a rotary evaporator to obtain a thick extract. Phytochemical screening results showed the presence of flavonoids, alkaloids, tannins, saponins, and phenolic compounds in ethanol extracts of papaya seeds. The antibacterial activity test of papaya seed ethanol extracts towards Staphylococcus aureus was carried out through in vitro by disc diffusion method with several concentrations. Antibacterial test showed that concentrations of 2%, 4%, and 6% of papaya seeds ethanol extracts was moderate antibacterial activity and at concentrations of 8% and 10% the antibacterial activity was classified as strong against Staphylococcus aureus.